A Comparison Principle for Some Types of Elliptic Equations. (2nd December 2012) - Amendola, Maria Emilia
Abstract : In this paper a comparison principle between a continuous viscosity supersolution and a continuous viscosity subsolution is presented. The operator of interest is a fully nonlinear uniformly elliptic one with a gradient term which could be noncontinuous and grow like some BMO functions, as shown in the last section.